Lumen-apposing covered self-expanding metal stent for management of benign gastrointestinal strictures - Majumder, Shounak; Buttar, Navtej S.; Gostout, Christopher; Levy, Michael J.; Martin, John; Petersen, Bret; Topazian, Mark; Wong Kee Song, Louis M.; Abu Dayyeh, Barham K. (Endoscopy International Open, 2016)
Background and aims: Self-expanding metal stents (SEMS) are safe and effective for endoscopic management of malignant gastrointestinal strictures, but there is limited experience with their use in refractory benign strictures. We assessed the use of a new lumen-apposing covered SEMS for the management of benign gastrointestinal strictures. Methods: A single-center case-series of five patients who underwent lumen-apposing covered SEMS placement for benign gastrointestinal strictures.Results: Three patients had a benign gastroduodenal stricture, one had a distal colonic anastomotic stricture, and one with complete gastrojejunal anastomotic stenosis underwent endoscopic creation of a new gastrojejunostomy. None of the patients developed any immediate or delayed stent-related adverse events. In two patients, the stents were left in place indefinitely. Stents were removed from the other three patients with successful resolution of their symptoms during follow-up.Conclusion: Lumen-apposing, fully covered SEMS appear to be safe and effective for management of selected benign gastrointestinal strictures.